1987
DOI: 10.1089/dna.1987.6.1
|View full text |Cite
|
Sign up to set email alerts
|

The P450 Gene Superfamily: Recommended Nomenclature

Abstract: A nomenclature for the P450 gene superfamily is proposed based on evolution. Recommendations include Roman numerals for distinct gene families, capital letters for subfamilies, and Arabic numerals for individual genes. An updating of this list, which presently includes 65 entries, will be required every 1-2 years. Assignment of orthologous genes is presently uncertain in some cases--between widely diverged species and especially in the P450II family due to the large number of genes. As more is known, it might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
236
0
16

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(255 citation statements)
references
References 32 publications
3
236
0
16
Order By: Relevance
“…The P450 family comprises at least five subfamilies, designated A to E (1). During biotransformation, the coded enzymes mediate phase I reactions in which xenobiotics are activated to reactive intermediate substances.…”
Section: A Leichsenring Et Almentioning
confidence: 99%
“…The P450 family comprises at least five subfamilies, designated A to E (1). During biotransformation, the coded enzymes mediate phase I reactions in which xenobiotics are activated to reactive intermediate substances.…”
Section: A Leichsenring Et Almentioning
confidence: 99%
“…Of these P-450s, P-45Oc (new nomenclature: P-450IA1 [2]) is distributed fairly ubiquitously in various tissues in rats and is induced by the administration of inducers such as 3-methylcholanthrene and 2,3,7,8-tetrachlorodibenzodioxin [3,4]. Severallaboratories have attempted to reveal the molecular mechanisms of the induction phenomena, using the DNA transfection technique [5 -91.…”
mentioning
confidence: 99%
“…Animal studies provided the first unequivocal evidence that cytochrome P450 exists in a number of multiple forms (Lu & West, 1980). One subfamily of the P-450 superfamily is represented by two forms of P-450 which are susceptible to induction by polycyclic aromatic hydrocarbons (the major inductive component of cigarette smoke) and has been named P-450I (Nebert et al, 1987). The two human P-450Is have been isolated and sequenced and shown to be equivalent to animal polycyclic hydrocarboninduced P-450s.…”
Section: Discussionmentioning
confidence: 99%
“…The two human P-450Is have been isolated and sequenced and shown to be equivalent to animal polycyclic hydrocarboninduced P-450s. Anticonvulsant drugs (for which phenobarbitone has been the prototype) are responsible for induction of the distinct subfamily P-4501IB (Nebert et al, 1987). Early studies (Sladek & Mannering, 1969) demonstrated that the effects of the above types of inducers could be additive, at least in animals.…”
Section: Discussionmentioning
confidence: 99%